Nest secondary plants and their associations with haemosporidian blood parasites in blue tit females - Jorge García-Campa; Sonia González-Braojos; Judith Morales (Parasitology)
Avian nests often contain aromatic plant fragments, which has led to propose among others that they repel ectoparasites or vectors of blood parasites (‘nest protection hypothesis’). To date, the relationship between secondary plant provisioning and the parent's blood parasites remains unexplored. We investigated whether the presence of secondary plants in nests during different reproductive stages (before incubation, during incubation and nestling period) was associated with the presence of nest-dwelling ectoparasites and females’ blood-parasite infections in blue tits (Cyanistes caeruleus) during chick rearing. In this species, females are highly exposed to parasites, particularly at the beginning of the breeding season, since they build the nest and incubate alone. They also brood the nestlings while the male assists with provisioning. We found that females that provided fewer plants before incubation were more likely to be infected by Plasmodium. Specifically, Females that did not provide Achillea herbs before incubation were more likely to be infected by both Plasmodium and Haemoproteus, reinforcing the ‘nest protection’ hypothesis. Thus, secondary plants may create an early environment that masks the odour of hosts or repels vectors. Surprisingly, the presence of Lavandula during the nestling period was positively related to Leucocytozoon infection. Given its fastest development among haemosporidians, we speculate that Lavandula herbs are provided by females to reduce mother-to-offspring transmission or as a self-medication strategy. Finally, the number of plant fragments provided before incubation was negatively associated with the number of (Protocalliphora azurea) larvae, whereas there were no associations with the presence of mites (Dermanyssus gallinoides).